2012
DOI: 10.1002/jnr.23042
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous firing and evoked responses of spinal nociceptive neurons are attenuated by blockade of P2X3 and P2X2/3 receptors in inflamed rats

Abstract: P2X3 and P2X2/3 receptors are selectively expressed on primary afferent nociceptors and have been implicated in modulating nociception in different models of pathological pain, including inflammatory pain. In an effort to delineate further the role of P2X3 receptors (homomeric and heteromeric) in the modulation of nociceptive transmission after a chronic inflammation injury, A-317491, a potent and selective P2X3-P2X2/3 antagonist, was administered to CFA-inflamed rats in order to examine its effects on respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…During the inflammatory process in peripheral tissue, neither prostaglandins nor sympathetic amines can sensitize primary afferent neurons by themselves; they depend on previous neuronal P2X3 receptor activation [103]. Spontaneous and evoked responses of spinal nociceptive neurons are attenuated by P2X3 receptor antagonism in inflamed rats [104]. Data has been presented to indicate that antagonism of spinal P2X3/P2X2/3 receptors regulates an indirect activation of the opioid system to alleviate inflammatory hyperalgesia [105].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…During the inflammatory process in peripheral tissue, neither prostaglandins nor sympathetic amines can sensitize primary afferent neurons by themselves; they depend on previous neuronal P2X3 receptor activation [103]. Spontaneous and evoked responses of spinal nociceptive neurons are attenuated by P2X3 receptor antagonism in inflamed rats [104]. Data has been presented to indicate that antagonism of spinal P2X3/P2X2/3 receptors regulates an indirect activation of the opioid system to alleviate inflammatory hyperalgesia [105].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…However, recent study revealed the prevailing expression of P2X3 subunits in dorsal root ganglion neurons in primates, including human sensory neurons (Serrano et al, 2012). Thus, the contribution of P2X2/3 receptors to chronic pain is probably more important at the level of nociceptive pathways within the spinal dorsal horn as indicated by the inhibition of nociceptive neuron firing by A-317491, a potent P2X2/3 antagonist (Xu et al, 2012). …”
Section: Functional Role Of Desensitization Of P2x3 Receptorsmentioning
confidence: 99%
“…We chose ATP for two reasons: it represents the challenge that upregulated A1AR in our conditions, and it is the main mediator released in the spinal cord during chronic conditions, including neuropathic pain, which regulates microglia migration and activation (Coull et al, ; Chen et al, ; Clark et al, ,b). Finally, we pharmacologically manipulated microglia in vitro , before and after ATP incubation, and then applied microglia onto the spinal cord by simultaneously recording the spontaneous and evoked activity of nociceptive‐specific (NS) neurons (McGaraughty et al, ; Xu et al, ). In these experiments, cells were also pretreated with 5′‐chloro‐5′‐deoxy‐(±)‐ENBA, a selective A1AR agonist, following ATP stimulation and applied to the spinal cord.…”
Section: Introductionmentioning
confidence: 99%